2007
DOI: 10.1186/1744-9081-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Two inbred rat strains contrasting for anxiety-related behaviors show similar levels of defensive responses to cat odor

Abstract: Rodents are known to display fear-related responses when exposed to the odor of natural predators, such as cats, even when they are totally naïve to these stimuli. Based on that, a behavioral test in which rats are exposed to cat odor has been developed and proposed to model some forms of anxiety. The objective of the present study was thus to compare the LEW (Lewis) and SHR (spontaneously hypertensive rats) inbred rat strains, which display genetic differences in other classical models of anxiety, in the cat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Likewise, Hemsworth and Barnett (2000) reported that experience with humans results in stimulus-specific effects rather than effects on general fearfulness or anxiety. Although rats exhibited an increased latency to consume a food treat in the presence of cat odour as expected, the handling treatments did not alter this response, consistent with previous studies showing that the response of rats to a predatory odour is robust in the face of genetic and environmental variability (Brüske et al, 2007;Roy et al, 2001).…”
Section: Effects Of Handling Experiencesupporting
confidence: 90%
“…Likewise, Hemsworth and Barnett (2000) reported that experience with humans results in stimulus-specific effects rather than effects on general fearfulness or anxiety. Although rats exhibited an increased latency to consume a food treat in the presence of cat odour as expected, the handling treatments did not alter this response, consistent with previous studies showing that the response of rats to a predatory odour is robust in the face of genetic and environmental variability (Brüske et al, 2007;Roy et al, 2001).…”
Section: Effects Of Handling Experiencesupporting
confidence: 90%
“…Hyperactivity of sympathetic premotor neurons [11,12] and changes in baroreflex sensitivity indicate autonomic impairments in SHR [13,14]. In addition, SHR present alterations in the psychogenic reactivity to different aversive and stressful paradigms [15][16][17][18][19][20]. In humans, the post-ganglionic sympathetic signal was higher in subjects reported for displaying white coat syndrome, when compared to borderline hypertensives.…”
Section: Introductionmentioning
confidence: 99%
“…The degree with which these variations explain the behavioral differences is not fully understood, but the use of behaviorally distinct strains might represent an important model to study the pharmacological and neurobiological correlates of behavior (Finn, Rutledge-Gorman, & Crabbe, 2003;Kalueff, Wheaton, & Murphy, 2007;Singewald, 2007;van der Staay, Arndt, & Nordquist, 2009). In this direction, mouse and rat inbred strains have been shown to differ in anxiety-like behavior and impulsivity (Brüske, Vendruscolo, & Ramos, 2007;Kangerski, Basso, Assreuy, Vendruscolo, & Takahashi, 2002;Neophytou et al, 2000;Ramos, Berton, Mormède, & Chaouloff, 1997;Trullas & Skolnick, 1993). The use of genetically tractable organisms, including invertebrate models and non-mammalian vertebrates, could generate important information regarding the genetic architecture underlying these disorders (Gerlai, 2010).…”
Section: Introductionmentioning
confidence: 99%